Determination of Total Phenolic Content of Ethanol Extract of Broken Bone Twigs (Euphorbia tirucalli Linn.) by Folin-Ciocalteu Method Spectrophotometrically - Zulfisa Zulfisa; Renatalia Fika; Muhajri Agusfina; Yonrizon Yonrizon; Abdah Muhsanah (Sean Institute, 2023)
This study aims to determine the total phenolic content of ethanol extracts of Broken Bone Twigs (Euphorbia tirucalli Linn.) Spectrophotometrically. Broken bone twigs (Euphorbia tirucalli Linn.) were extracted using maceration method with ethanol solvent. Total phenolic content was determined using Visible Spectrophotometric method with Folincio-Calteu reagent. The principle of this method is the formation of a blue complex compound of Fossosmolibdat-phosphotungstad reduced phenolic compounds in an alkaline atmosphere that can be measured Spectrophotometrically. As a comparator used gallic acid. From the results of absorbance measurements obtained linear regression equation ŷ = 0.0012x + 0.0316 with a coefficient of determination (R²) of 0.9661. Phenolic levels in bone fracture twigs (Euphorbia tirucalli Linn.) amounted to 0.102% w/b calculated as gallic acid.